Phytophthora palmivora, the causal agent of bud rot disease of oil palm (Elaeis guineensis Jacq.): Biology, detection and control - Mohamed, Maizatul-Suriza (2017)
Bud rot disease has been considered as a devastating disease of oil palm in Latin America. Severe outbreaks of this disease have been reported in Colombia, Brazil, Ecuador, Panama and Suriname. The causal agent of bud rot disease in Colombia has been identified as Phytophthora palmivora. This pathogen is known to be responsible for several tropical diseases such as black pod and stem canker disease of cocoa, especially during the rainy season. Phytophthora palmivora has also been reported to attack durian, rubber, pepper and jackfruit causing diseases in various parts of the plant such as fruit, leaves and stems. However, no outbreaks of the disease have been reported in oil palm in Malaysia or other Southeast Asian countries. Several aspects of research need to be conducted to understand why this pathogen causes problems in oil palm in South America but not in Southeast Asia. This study aimed to analyze variation between the Colombian P. palmivora isolates that cause bud rot disease in comparison with Malaysian isolates and other isolates gathered from different hosts and regions. Our hypothesis was that P. palmivora isolates from the different regions and/or hosts have different molecular characteristics and have dissimilar levels of pathogenicity. Sequence alignments of several genetic markers, the internal transcribed spacer (ITS) of the ribosomal RNA (rRNA) gene cluster, beta-tubulin (β-tubulin), translation elongation factor 1 alpha (EF-1α), cytochrome c oxidase subunit I (CoxI) and subunit II (CoxII) genes failed to distinguish between Colombian oil palm isolates and P. palmivora from different hosts and regions. It was concluded that these markers are more suitable for inter-specific studies between species but not for intra-specific evaluation within species of P. palmivora. However, a new marker named as P. palmivora hypothetical avirulence effector protein (PpHPAVR) along with analyses of amplified fragment length polymorphisms (AFLPs), separated the Malaysian and Colombian isolates into distinct clades. This indicates that there is genomic variation within P. palmivora isolates. The zoospores of P. palmivora from various hosts and demographic origin were shown to have the ability to cause infection to oil palm seedlings, durian and rubber. However, not enough evidence has been collected to confirm that pathogenicity correlates with the distinct clades observed with AFLPs and PpHPAVR. Phytophthora palmivora species-specific diagnostic using PCR and loop-mediated isothermal amplification (LAMP) have been developed based on the PpHPAVR region.